Introduction. Intergroup prejudice from a developmental and social approach - Enesco, Ileana; Guerrero, Silvia (Anales de Psicología / Annals of Psychology, 2011)
The aim of this Special Issue is to gather research from developmental and social psychologists, from Spain and other countries, in the broad area of prejudice and intergroup attitudes. The Monograph includes review papers and empirical studies that present different theoretical assumptions, research procedures, and types of population. Most contributions are related to the study of children’s and youth’s attitudes toward different racial-ethnic groups, ingroup bias or ethnic identity, and three articles address other forms of prejudice that have an undeniable social significance in our Western societies: biases toward homosexuality, disability, and body size.